Isolation of Mesophilic Sulphate-Reducing Bacteria from a Microbial Community: Comparative Study of the Effect of pH and Dissolved Heavy Metals on the Reduction of Sulphate - Kikot, Pamela Alejandra (2009)
Metallurgical processes and mining are the main source of heavy metal contamination of water sources, rivers and lakes. There are a large number of physicochemical processes that can be applied for the immobilization of heavy metals from a liquid matrix. However, many of them are not particularly desirable because their low selectivity and inefficiency when high volumes of low metal concentration liquids must be treated. In such conditions, alternative biological processes have shown to be more useful than traditional physicochemical processes. One of those processes, bioprecipitation of metal sulphides is relevant due to the possibility of forming stable solids (very low solubility) with small volumes compared with other solids. This process is mediated by a broad group of organisms called sulphate reducers that are able to catalyze, under anaerobic conditions, the reduction of sulphate with organic compounds as electron donors. In this paper, we study the effect of the presence of various heavy metals and the pH on the ability to reduce sulphate by sulphate-reducing bacteria. We compare the reduction of sulphate by a microbial community obtained from the effluent of a tannery with a strain isolated from that community. Our results showed that sulphate reduction was significantly affected by pH changes whereas the presence of heavy metals did not show a significant effect. In addition, metal precipitation by the isolated strain was similar than that produced by the community.